BETLE LEAF ESSENTIAL OIL FOR HEMOPHILIAC PATIENTS AND ITS ANTIBACTERIAL EFFECTS ON MYCOBACTERIUM TUBERCULOSIS - Sucipto, Teguh Hari; Aisyah, Nourmalasari; Lestari, Puji; Setyawati, Harsasi (Institute of Topical Disease Universitas Airlangga, 2016)
Betle leaf (Piper betle L.) is a medicinal plant. It contains essential oil and shows various biological activities, such as antibacterial, anticoagulant, etc. It is further reported to have low anticoagulant activities; thus, it is highly potential as a candidate for coagulant drug. Coagulant is used to prevent bleeding for patients with blood clotting disorders like hemophilia. In Indonesia, 1,236 people were reported with hemophilia. The standard parameters of anticoagulant activity are the freezing period and the compound concentrations. The purpose of this study was to determine the effect of betle leaf's essential oil on blood coagulation in patients with factor VIII and IX of blood plasma disorders. The isolation of essential oil is conducted through steam distillation method with two kinds of solvents, namely distilled water and n-hexane. The obtained n-hexane extract is then separated from the liquid-liquid extraction and rotary evaporator. Essential oil is diluted with citrate plasma solution. The test results of blood clots increase as the concentration of essential oils increase. The results are recorded as such: essential oils ½ times dilution of 99.67 seconds; ¼ times dilution of 127 seconds; 1/8 times dilution of 179 seconds; and 1/16 times dilution of 242.67 seconds. The test above proves that the piper betle extract possesses a coagulant activity. The ethanol extract contained in the piper betle could stimulate clotting in the blood cells. It is caused by the increase of blood plasma concentration which further escalate the plasma fluid into the blood cells. Based on this study, the activity of Mycobacterium tuberculosis can be obstructed by betle leaf in ½ times dilution. The extract significantly reduces acid which accelerates bacteria development.